The role of baseline and post-treatment frontal QRS-T angle for detecting arterial blood pressure control. (19th May 2021) - Mansiroglu, Asli Kurtar; Coşgun, Mehmet; Sincer, Isa; Gunes, Yilmaz
ABSTRACT: Objectives : In this study, we aimed to investigate the value of the frontal QRS-T angle (f(QRS-T)) in determining blood pressure control among newly diagnosed hypertensive patients with no left ventricular hypertrophy. Methods : Fifty patients with newly diagnosed hypertension were included in this single-center study. The patients were examined with 12-lead ECGs and 24-hour ambulatory blood pressure monitoring (24 h-ABPM) before and 1 month after antihypertensive treatment. Results : Baseline and post-treatment f(QRS-T) angle values were observed to be similar (38.0 [0.0–174.0] and 37.0 [1.0–139.0], respectively; p = .827). The values of QT minimum ( p = .006), QTc mean ( p = .030), Tp-e ( p = .027), and JTc ( p = .010) significantly decreased after control of blood pressure. Conclusions : The f(QRS-T) angle, which can be easily calculated on the ECG, is not a useful tool to determine hypertension control at early stage in newly diagnosed hypertensive patients.